Decline in child vaccination coverage during the COVID‐19 pandemic — Michigan Care Improvement Registry, May 2016‐May 2020. Issue 7 (28th June 2020) - Bramer, Cristi A.; Kimmins, Lynsey M.; Swanson, Robert; Kuo, Jeremy; Vranesich, Patricia; Jacques‐Carroll, Lisa A.; Shen, Angela K.
Abstract : This article describes a reduction in childhood vaccinations during the COVID‐19 pandemic, which may leave communities more vulnerable to vaccine‐preventable diseases.